Визначення вмісту 59Ni та 55Fe в конструкційних елементах АЕС - Zheltonozhsky, V.O.; Myznikov, D.E.; Savrasov, A.M.; Slisenko, V.I. (Publishing house "Academperiodika", 2023)
The structural materials from the 2nd unit of the Chornobyl NPP were irradiated by bremsstrahlung photons with an end-point energy of 37 MeV. From the measured y-spectra, using the ratios among the 57Co, 54Mn, and 58Co activities, the concentrations of 58Ni and 56Fe isotopes were determined in compare with the concentrations of 59Co. Using the obtained data and the measured 60Co activity in the studied samples, we developed a method for determining the 59Ni and 55Fe activities. Radiochemical validation of the created method was performed, and good quantitative agreement of 59Ni and 55Fe activities obtained by spectroscopic and radiochemical methods was found.